2018
DOI: 10.1007/s10549-018-4833-8
|View full text |Cite
|
Sign up to set email alerts
|

Syntenin1/MDA-9 (SDCBP) induces immune evasion in triple-negative breast cancer by upregulating PD-L1

Abstract: Syntenin1 exhibits a profound function in mediating T cells apoptosis by upregulating PD-L1 and thus could be used as a prognostic biomarker of TNBC. Tumoural syntenin1 expression corelated with anti-PD-L1 treatment efficacy. Targeting syntenin1-mediated T-cell suppression could be a potential strategy for improving the prognosis of patients with TNBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 32 publications
0
22
1
Order By: Relevance
“…Another study has shown that syntenin1 is highly expressed in TNBC tissues and increases the expression level of PD-L1 by activating STAT3, consequently attenuates the response of TNBC to anti-PD-L1 treatment [74]. Moreover, direct inhibition of STAT3 overcomes the resistance of TNBC to immunotherapies, which confirms its immunosuppressive activity [72, 74].…”
Section: The Stat3 Signaling Pathway In Triple Negative Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Another study has shown that syntenin1 is highly expressed in TNBC tissues and increases the expression level of PD-L1 by activating STAT3, consequently attenuates the response of TNBC to anti-PD-L1 treatment [74]. Moreover, direct inhibition of STAT3 overcomes the resistance of TNBC to immunotherapies, which confirms its immunosuppressive activity [72, 74].…”
Section: The Stat3 Signaling Pathway In Triple Negative Breast Cancermentioning
confidence: 99%
“…The mechanism studies have shown that pSTAT1 and pSTAT3 form heterodimers in the cytoplasm and translocate into the nucleus, where the pSTAT1-pSTAT3 dimers bind to the PD-L1 promoter and activate its transcription [72]. Another study has shown that syntenin1 is highly expressed in TNBC tissues and increases the expression level of PD-L1 by activating STAT3, consequently attenuates the response of TNBC to anti-PD-L1 treatment [74]. Moreover, direct inhibition of STAT3 overcomes the resistance of TNBC to immunotherapies, which confirms its immunosuppressive activity [72, 74].…”
Section: The Stat3 Signaling Pathway In Triple Negative Breast Cancermentioning
confidence: 99%
“…Anti-CTLA-4 treatment reduces the activation threshold of T cells and magnifies the tumor-specific immune response [89, 90]. Some studies revealed that anti-CTLA-4 mAb could selectively eradicate Tregs by antibody-dependent cell-mediated cytotoxicity (ADCC) effect [91, 92].…”
Section: Introductionmentioning
confidence: 99%
“…SDCBP (also known as Syntenin) is a PDZ domain scaffolding protein that binds Syndecan (Grootjans et al 1997) and regulates exosome formation (Baietti et al 2012). SDCBP has been associated with worse breast cancer outcome that has been attributed to multiple mechanisms, including tumor cell proliferation, invasiveness, and evasion of the antitumor immunity (Liu et al 2018; Yang et al 2013; Qian et al 2013; Koo et al 2002). To our knowledge, this study is the first to link SDCBP with a potential role in breast cancer incidence, which is supported by its close proximity to the rs4305889 [G] risk allele (Kuchenbaecker et al 2014).…”
Section: Resultsmentioning
confidence: 99%